Beispiel Nr: 16
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x +4 y =4\\ -\frac{1}{2} x +3 y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ I \qquad 2 x +4 y =4 \qquad / \cdot\frac{1}{2}\\ II \qquad -\frac{1}{2} x +3 y = 3 \qquad / \cdot2\\ I \qquad 1 x +2 y =2\\ II \qquad -1 x +6 y = 6 \\ \text{I + II}\\ I \qquad 1 x -1 x+2 y +6 y =2 +6\\ 8 y = 8 \qquad /:8 \\ y = \frac{8}{8} \\ y=1 \\ \text{y in I}\\ I \qquad 2 x +4\cdot 1 =4 \\ 2 x +4 =4 \qquad / -4 \\ 2 x =4 -4 \\ 2 x =0 \qquad / :2 \\ x = \frac{0}{2} \\ x=0 \\ L=\{0/1\} \end{array} & \begin{array}{l} \\I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ I \qquad 2 x +4 y =4 \qquad / \cdot3\\ II \qquad -\frac{1}{2} x +3 y = 3 \qquad / \cdot\left(-4\right)\\ I \qquad 6 x +12 y =12\\ II \qquad 2 x -12 y = -12 \\ \text{I + II}\\ I \qquad 6 x +2 x+12 y -12 y =12 -12\\ 8 x = 0 \qquad /:8 \\ x = \frac{0}{8} \\ x=0 \\ \text{x in I}\\ I \qquad 2 \cdot 0 +4y =4 \\ 4 y +0 =4 \qquad / -0 \\ 4 y =4 -0 \\ 4 y =4 \qquad / :4 \\ y = \frac{4}{4} \\ y=1 \\ L=\{0/1\} \end{array} \end{array} $